Empowerment of Santri at Padepokan Siti Dhumillah, Bogor: A Productivity Improvement Program Through Processing Farm Products as Agribusiness and Business Education. - Ahmad Maulidizen; Risman Nugraha; Muhammad Alfriandra Hedza Ramadhan; Niken Chaerunisa; Fadel Hafidh Isman; Adiva Aura Assyari; Muhammad Zailani Iman (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This community service program aims to enhance the productivity of students (santri) at Padepokan Siti Dhumillah, Bogor, by leveraging agribusiness and business education approaches. Utilizing local agricultural produce such as chili peppers and tomatoes, the program fosters value-added product innovation through the production of sambal under the brand